Impact of prolonged cardiopulmonary bypass on gastrointestinal complications in cardiac surgery: a retrospective cohort study - Xiaofang Yang; Ning Lu; Luxi Yang; Boxia Li; Wenjun Zhou; Yuanmin Li; Bing Song; Jinqiu Yuan; Wenbo Meng (Perioperative Medicine)
Abstract Background Gastrointestinal complications (GICs) following cardiac surgery with cardiopulmonary bypass (CPB) significantly impact postoperative recovery and clinical outcomes. Methods This single-center, retrospective cohort study evaluated the incidence, risk factors, and outcomes of GICs in patients undergoing cardiac surgery with CPB between January 2018 and December 2023. Patients were stratified by CPB duration (≥ 120 min vs. < 120 min). Propensity Score Matching (PSM) in a 1:2 ratio was used to control for baseline confounders. The primary outcome was the occurrence of GICs within 30 days post-surgery. Results Among 1444 patients, 686 had prolonged CPB duration, with an overall GICs incidence of 8.59% (124/1444). After PSM, the prolonged CPB group exhibited a significantly higher incidence of GICs compared to the normal CPB group (8.09% vs. 4.31%, p = 0.041). Multivariate logistic regression identified prolonged CPB duration (≥ 120 min; OR, 1.86; 95% CI, 1.06–3.26, p = 0.029), hypertension (OR 1.86; 95% CI, 1.01–3.44; p = 0.049), left ventricular ejection fraction (LVEF; OR, 0.92; 95% CI, 0.88–0.96; p < 0.001), and aortic surgery (OR, 2.72; 95% CI, 1.20–6.19; p = 0.017) as independent risk factors for GICs. Additionally, prolonged ventilator time and higher in-hospital costs were more prevalent in the prolonged CPB group. Conclusions Prolonged CPB (≥ 120 min), hypertension, LVEF, and aortic surgery are significant risk factors for GICs following cardiac surgery with CPB. Early identification of high-risk patients may facilitate timely intervention, reduce complications, and improve postoperative recovery outcomes. Trial registration ClinicalTrials.gov: NCT06697405. Graphical Abstract